The Differences and Similarities between English for Specific Purposes(ESP) and English for General Purposes(EGP) Teachers - Islam, Dr. Muhammad (Journal of Research in Humanities, 2023)
Thistheoretical study aims to explore the differences and similarities in the roles of English for specific purposes (ESP) and English for general purposes (EGP) teachers. It also highlights the implications of these differences and similarities for English language teaching (ELT), course materials and classroom practices.The review of previous studies reveals that EGP focuses on general English language abilities of students whereas ESP focuses on specific skills and needs of learners based on a detailed analysis of learners’ professional/academic needs. This distinction has important implications for ESP teachers. In addition to the role of a language teacher, an ESP practitioner has to assume certain special roles, for example, as a course designer, material provider, collaborator, researcher, evaluator and cultural interpreter. Therefore, the study recommends that special pre- and in-service training/refresher courses should be arranged for ESP teachers so that they may become equipped to perform challenging tasks related to their job.